Transcriptional Pausing in Vivo: A Nascent RNA Hairpin Restricts Lateral Movements of RNA Polymerase in Both Forward and Reverse Directions - Toulmé, Francine; Mosrin-Huaman, Christine; Artsimovitch, Irina; Rahmouni, A. Rachid (Journal of molecular biology, 2005)
Transcriptional pausing by RNA polymerase has been the subject of extensive investigations in vitro, yet little is known about its occurrence and significance in vivo. The transient nature of the pausing events makes them difficult to observe inside the cell, whereas their studies in vitro by classical biochemical methods are usually conducted under non-physiological conditions that increase the pause duration. Here, we have used an Escherichia coli system in which several RNA polymerase molecules transcribing in tandem traverse a pausing sequence while approaching a protein roadblock. The in vivo DNA footprinting and RNA 3′ end mapping of the elongation complexes are consistent with a dynamic view of the pausing event, during which RNA polymerase first loses its lateral stability and slides backward, and is subsequently rescued from extended backtracking and stabilized at the pause site by a nascent RNA hairpin. Our results show also that the folding of the hairpin provides an assisting force that promotes forward translocation of a trailing polymerase under a strained configuration by balancing the opposing force created by a steric clash with a leading elongation complex.